“Tiki Talk”: Voices and Meanings of the ‘I‘ipona Statues, Hiva‘oa (Marquesas Islands). - Nerici, Giacomo; Koch, Michael J. (Waka Kuaka, 2023)
This paper aims to show how current knowledge concerning the tiki (sculptures) of the ‘I‘ipona me‘ae (temple site), in Hiva‘oa (Marquesas Islands), has been constructed on the basis of a constant flow of information and “talk” circulated over time. Encounters between locals and non-Marquesan specialists, sometimes resulting in differing stories or misunderstandings, have led to the affirmation of some cultural versions of history over others and have allowed certain individuals to legitimise themselves as “cultural bridge-makers” (passeurs culturels). Hidden for decades in vegetation and the subject of cultural loss and demonisation, the ‘I‘ipona me‘ae was restored in the 1990s and more recently included with other areas in the Marquesas project for inscription on the UNESCO World Heritage List. This marks a new attitude towards heritage that must be seen in connection with the process of Marquesan “cultural awakening” (since the 1980s) and the important role of archaeology in recovering ancient traditional places, but also within a broader tourist gaze and Western pop trends of commercialised “tiki images”. This article focuses on the cultural contexts and protagonists that have influenced the production of local legends (ha‘akakai) or stories as well as artistic and devotional attitudes towards the statues that have evolved. By exploring the liminal zones of encounter between native and foreign witnesses in both oral and written sources, we attempt to examine “tiki talk” and thus several negotiated, hybrid and often creative interpretations of the traditional past.